Palliative care at home: a literature review - Coelho, Sílvia Patrícia (2016)
Introduction: Palliative care promotes a holistic care, promoting a centered care to the patient and, thus contributing to the comfort and quality of life by addressing the problems associated with life-threatening diseases, preventing and relieving suffering. Aims: Identify the evidence produced about home palliative care. Materials and methods: A integrative review on the data- bases of ISI Web of Knowledge, CINHAL, MEDLINE and PubMed, B-on with the descriptors “palliative care”, “home care”, “nursing care”. Articles in the English language, existing in full text, with abstract and references available and analyzed by experts were included. Results: A total of 69 articles were found and analyzed. The majority of the articles found are: original studies, literature reviews, editorials and commentaries. The most discussed topics were: home palliative care, family sup- port, home care, symptom control and promoting quality of life. There is predominance in the last decade especially in 2009-2012 and the predominant language was English. The research reveals the increasing number of patients with progressive and incurable diseases and 68,2% of patients prefer die at home. It becomes essential to develop a network of care extended to cover the home assistance. Conclusion: We observed that palliative care should improve social and innovative health policies, centered on the needs and preferences of patients, associating scientific knowledge, skills and attitudes in order to develop the excellence of care. According to the evidence found the development of a specialized care, implementing effective interventions which provide a dignified death, and supporting the family throughout the process including the stage of grief, contributes for an individualized approach focused on the problems of patients and families, in symptom control and maximizing comfort.